2009
DOI: 10.1158/0008-5472.can-08-2499
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transforming Growth Factor-β–Mediated Immunosuppression in Tumor-Draining Lymph Nodes Augments Antitumor Responses by Various Immunologic Cell Types

Abstract: Tumor-draining lymph nodes (DLN) are the most important priming sites for generation of antitumor immune responses. They are also the location where an immunosuppressive cytokine, transforming growth factor-β (TGF-β), plays a critical role in suppressing these antitumor immune responses. We focused on TGF-β-mediated immunosuppression in DLNs and examined whether local inhibition of TGF-β augmented antitumor immune responses systemically in tumor-bearing mice models. For inhibition of TGF-β-mediated immunosuppr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
(24 reference statements)
1
26
0
Order By: Relevance
“…Anti-TGF-β antibody treatment also reverses the suppressive function of Tregs [30]. In the E.G7 tumor model, the effect of TGF-β inhibition was clearly shown in draining lymph nodes, in which suppression of Treg proliferation and an increase in the number of tumor antigen-specific CD4+ or CD8+ cells producing IFN-gamma was found [83]. However, one should note that while TGF-β is known to play a crucial role in CD4+Foxp3+ Treg cell induction, there are few reports to show that the improved immune responses from TGF-β antagonism is mediated by CD4 Treg cells ([79] and personal communication with Dr Lalage Wakefield).…”
Section: Antitumor Activity Of Tgf-β Inhibition Is Dependent On the Hmentioning
confidence: 99%
“…Anti-TGF-β antibody treatment also reverses the suppressive function of Tregs [30]. In the E.G7 tumor model, the effect of TGF-β inhibition was clearly shown in draining lymph nodes, in which suppression of Treg proliferation and an increase in the number of tumor antigen-specific CD4+ or CD8+ cells producing IFN-gamma was found [83]. However, one should note that while TGF-β is known to play a crucial role in CD4+Foxp3+ Treg cell induction, there are few reports to show that the improved immune responses from TGF-β antagonism is mediated by CD4 Treg cells ([79] and personal communication with Dr Lalage Wakefield).…”
Section: Antitumor Activity Of Tgf-β Inhibition Is Dependent On the Hmentioning
confidence: 99%
“…At present, several studies have focused on the therapeutic potential of antagonizing the TGFß pathway against cancer (12,13). The most advanced TGFß signaling antagonist in clinical development is large-molecule including monoclonal antibodies (14)(15)(16). During this decade, many small molecules to inhibit TGFß type I receptor have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fujita et al showed that inhibition of TGF-β suppressed the proliferation of regulatory T cells and increased the number of tumor antigen-specific CD4 + and CD8 + cells producing IFN-γ in mouse lymph nodes [11]. Taken together, these findings suggest that TGF-β suppresses antitumor immune responses within lymph nodes.…”
Section: Discussionmentioning
confidence: 91%
“…In these patients, moreover, production of TGF-β is often upregulated not only in the tumor cells but also in the stromal cells surrounding the tumor [9]. The paracrine TGF-β produced by these cells stimulates angiogenesis, suppresses immune responses [10,11], and increases the interaction of tumor cells with the extracellular matrix, leading to greater invasiveness [12].…”
Section: Introductionmentioning
confidence: 99%